Assessment of wind energy potential in the capital city of Chad, N’djamena - Didane, Djamal Hissein; Ab Wahab, Abas; Shamsudin, Syariful Syafiq; Rosly, Nurhayati; Zulkafli, Mohd Fadhli; Sofian, Mohd (American Institute of Physics, 2017)
In this study, statistical analysis of a long term meteorological data of 10 years have been presented to reveal the potential of wind power as a source of energy generation in the capital of Chad, N’Djamena. The recent ten-year period wind data were collected from the Hassan Djamous International Airport at N’Djamena. The wind characteristics and wind energy potential were analyzed using Weibull distribution function. The results show that the values of the shape parameter k, and scale parameter c, varied over a wide range. The annual highest values of the Weibull shape parameter k, and scale parameter c, were 1.59 and 4.12 m/s respectively. It was also found that higher wind speeds occurred during dry season, i.e. November to July and the lower wind speeds occurred during the wet season, i.e. August to October. The annual average of the most probable wind speed and wind speed carrying maximum energy were respectively 1.86 m/s and 6.48 m/s. Likewise, the wind power density was ranging between 55.96 W/m2 and 77.37 W/m2 and the corresponding annual energy density values ranged between 490 and 677 kWh/m2/year at 10 m height above ground. The highest wind power potential was found during the summer season which corresponds to the peak demand season of electricity in Chad. However, although the wind potential in this site is promising, it is concluded that it is adequate only for small-scale application.